Wireless wind energy data transmission system - Ahmad Kamil, Fadir (2009)
Wireless communications represent a rapidly emerging area of growth and importance for providing ubiquitous access to the network for all type of community. Nowadays, all community increasingly wants network access for general purpose at classrooms, meeting rooms, auditoriums, and even the hallways of campus buildings. Wireless communications can both support the institution mission and provide costeffective solutions. Wireless is being adopted for many new applications: to connect computers, to allow remote monitoring and data transceiver or acquisition, to provide access control and security, and to provide a solution for environments where wires may not be the best solution. Wireless technology will become our new life in the future.